Association between spicy food consumption and lipid profiles in adults: a nationwide population-based study. Issue 2 (4th July 2017) - Xue, Yong; He, Tingchao; Yu, Kai; Zhao, Ai; Zheng, Wei; Zhang, Yumei; Zhu, Baoli
Abstract: CVD remains the leading cause of mortality worldwide, with abnormal lipid metabolism as a major risk factor. The aim of this study was to investigate associations between spicy food consumption and serum lipids in Chinese adults. Data were extracted from the 2009 phase of the China Health and Nutrition Survey, consisting of 6774 apparently healthy Chinese adults aged 18–65 years. The frequency of consumption and degree of pungency of spicy food were self-reported, and regular spicy food consumption was assessed using three consecutive 24-h recalls. Total cholesterol, TAG, LDL-cholesterol and HDL-cholesterol in fasting serum were measured. Multilevel mixed-effects models were constructed to estimate associations between spicy food consumption and serum lipid profiles. The results showed that the frequency and the average amount of spicy food intake were both inversely associated with LDL-cholesterol and LDL-cholesterol:HDL-cholesterol ratio (all P for trend <0·05) after adjustment for potential confounders and cluster effects. HDL-cholesterol in participants who usually consumed spicy food (≥5 times/week) and who consumed spicy food perceived as moderate in pungency were significantly higher than those who did not (both P <0·01). The frequency and the average amount of spicy food intake and the degree of pungency in spicy food were positively associated with TAG (all P for trend <0·05). Spicy food consumption was inversely associated with serum cholesterol and positively associated with serum TAG, and additional studies are needed to confirm the findings as well as to elucidate the potential roles of spicy food consumption in lipid metabolism.